MODEL HUBUNGAN KECEPATAN – VOLUME – KEPADATAN ARUS LALU LINTAS PADA RUAS JALAN ARTERI DI KOTAPALU (Studi kasus: Jl. Trans Sulawesi Kota Palu) - Mashuri, Mashuri (MEKTEK, 2006)
There are three main traffic flow characteristics which are used to estimate the level of services of a road link, i.e traffic Speed (S), traffic Volume (V) and traffic Density (D). In Traffic engineering theory, three models are often used for modeling of traffic flow characteristics. They are Greenshield model, Greenberg model and Underwood Model respectively.The aim of this research is to find the relationship model between Speed characteristic (S) – Volume characteristic (V) – Density characteristic (D) on Trans Sulawesi street in Palu city. Collected data is volume and time distance of traffic passing on specific road segment . Time distance data is needed for finding speed of traffic data. For collecting of time distance data, we choice the segment is 50 m long.The result of this research indicates that the Greenshield model is most realistic model in study location